(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study examines the impact of artificial intelligence (AI) technologies on the development of internal communication strategies in Saudi governmental institutions, within the framework of the Kingdom’s Vision 2030 digital transformation. Employing a qualitative approach, the research is grounded in the strategic communication model by Rolfs, highlighting the integration between AI tools and communicative effectiveness. The findings reveal that AI plays a vital role in enhancing internal communication through content automation, message personalization, interaction analysis, and real-time response measurement. The study emphasizes that the success of AI adoption depends on leadership with a clear digital vision and the strategic restructuring of communication to foster transparency, participation, and operational efficiency. It provides practical recommendations for government institutions to integrate AI tools within structured communication planning, transforming these technologies from optional tools into strategic elements that enrich institutional performance and strengthen organizational culture.